Effects of Co-Administration of Lycopene and / or Zinc on Serum Electrolyte In Alloxan- Induced Diabetic Wistar Rat - A.D.T, Goji; K.A, Muhammed; J.A, Tende; I, Aisha (Journal of Medical Biomedical and Applied Sciences, 2018)
Background: The incidence of diabetes is increasing rapidly with interference in electrolytes sodium (Na+), potassium (K+) and chloride (Cl-). This work was designed to study the effects of co-administration of Lycopene and/or Zinc on Serum Electrolyte in Alloxan- Induced Diabetic Wistar Rat. Material and Methods: Healthy albino rats weighing between 150g and 200g were used. The rats were randomly allotted into six groups, each containing five albino rats respectively. Five of the groups ( II,III IV V and VI) were induced with diabetes by single intraperitoneal (i.p) injection of freshly prepared in 0.1 mol/L citrate buffered solution (pH 4.5) of streptozotocin (Sigma Aldrich, St. Louis, MO, USA) at a dose of 150 mg/kg body weight. Control (vehicle) rats were injected with equal volume of 0.1 mol/L citrate buffer. Four days after Alloxan injection, diabetes induction was confirmed by measuring fasting blood glucose level in a tail vein blood samples using ACCU-CHEK compact plus glucometer (Roche, France). Rats with glucose level of 200 mg/dl or higher were considered as diabetic. After the induction of diabetes the rats were treated using the Lycopene and Zinc separately and in combination respectively according to group daily, whereas, the other group (I) was not given any treatment and this served as the normal control, providing a baseline data. Results: The diabetic treated groups had significantly (P < 0.05) higher serum Na+ concentration than the diabetic control group. The diabetic treated groups had significantly (P < 0.05) lower serum K+ concentration than the diabetic control. Also, the diabetic treated groups had significantly (P < 0.05) higher Clô€€€ concentration than the diabetic control group. The diabetic treated group had significantly (P < 0.05) lower HCO3 ô€€€ concentration than the diabetic control group. The diabetic treated groups had significantly (P < 0.05) lower serum urea concentration when compared to the diabetic control. The diabetic treated groups showed significantly (P < 0.05) decrease in serum creatinine concentration as compared to the diabetic control group. Conclusion: These anomalies were all ameliorated to about normal values after four weeks of treatment with Lycopene+Zinc. This suggests the synergistic beneficial effects of lycopene acid and zinc against alloxan-induced diabetes in Wistar Rats.